Evaluation of Normalized Difference Vegetation Index by Remote Sensing with Landsat Satelites in the Tayacaja Valley in the Central Andes of Peru - Carbajal Morán, Hipólito (2023)
The research sought to evaluate the normalized difference vegetation index (NDVI) of the study area located in the province of Tayacaja, which includes the districts of Acraquia, Ahuaycha, Pampas and Daniel Hernández, which is part of the central Andes of Peru. The data were collected in low water seasons with a longitudinal cut of 30 years with one sample per year, starting in 1993 until 2022; these samples corresponded to the month of August of each year. The images were extracted from maps from Landsat satellite databases, which were filtered for low cloud cover to avoid interference with the images. Maps from 1993 to 2012 were obtained from Landsat 5 satellite, while from 2013 to 2022 data were obtained from Landsat 8 satellite. The normalized difference vegetation index was determined using Quantum GIS based on the red and near infrared maps; being the minimum NDVI value obtained -0.18, which corresponds to the aquatic body of the Upamayu River that crosses from west to east the study area; while the highest NDVI obtained was 0.79 indicating a greater vegetation cover constituted by mainly eucalyptus plants. The mean NDVI of the 30 years is close to 0.21; this is an indicator that the vegetation is scarce and that it is decreasing mainly due to population growth.